1994
DOI: 10.1002/mpo.2950220502
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of in vitro drug resistance testing in childhood acute lymphoblastic leukemia: The state of the art

Abstract: Nowadays about two-thirds of children with acute lymphoblastic leukemia (ALL) can be cured with chemotherapy, but one-third die from the disease. The clinical response of leukemic cells to chemotherapy is roughly due to two factors: the effective drug levels reaching the cells and the resistance of these cells to the drugs. The clinical value of cellular drug resistance in children with ALL is not known. We developed an in vitro assay to study drug resistance in these children. In this article, the main result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 33 publications
0
12
0
2
Order By: Relevance
“…This breakthrough idea made subsequent gains possible. Clinical and laboratory observations linking treatment outcome to glucocorticoid steroid sensitivity 75,76 and our demonstration of the superiority of dexamethasone over prednisone 26 may provide additional opportunities. Further opportunities may derive from our observation that patients with a suboptimal response may be rescued with changes in therapy 6 weeks later.…”
Section: Discussionmentioning
confidence: 99%
“…This breakthrough idea made subsequent gains possible. Clinical and laboratory observations linking treatment outcome to glucocorticoid steroid sensitivity 75,76 and our demonstration of the superiority of dexamethasone over prednisone 26 may provide additional opportunities. Further opportunities may derive from our observation that patients with a suboptimal response may be rescued with changes in therapy 6 weeks later.…”
Section: Discussionmentioning
confidence: 99%
“…These conclusions fully warrant investigations of new biological prognostic markers ( Campana & Pui, 1995; Hecker et al , 1994 ; Kaspers et al , 1995 ; Pieters et al , 1994 ; Privitera et al , 1992 ; Steinherz et al , 1996 ; Uckun et al , 1995 ; McLean et al , 1996 ), whose value should be assessed not only by univariate analysis, but also taking into account the four main prognostic variables (WBC, age, sex and cytogenetics).…”
Section: Discussionmentioning
confidence: 94%
“…Although the leukaemic cell sample that was most resistant to 2‐CdA and araC was from a patient with T‐cell ALL, an immunophenotype often associated with an unfavourable outcome (Mahony, 1994), two T‐cell ALL samples in this study were also among those that were most sensitive to the nucleosides. Pieters et al (1994) have shown a wide variation in sensitivity to a number of antitumour agents in leukaemic blasts from patients with ALL. Campana et al (1993) also observed considerable interpatient variation in lymphoblast sensitivity to vincristine, 6‐thioguanine, araC and teniposide, using a novel stroma‐supported immunocytometric assay (SIA) to evaluate blasts from patients with ALL.…”
Section: Discussionmentioning
confidence: 99%
“…AraC was chosen for this comparison because of its current use in remission induction and consolidation protocols in ALL therapy; araC has also been used in combinations prophylactically, to reduce the possibility of central nervous system (CNS) involvement in childhood ALL (Morra et al , 1993). Pieters and colleagues (Pieters et al , 1994; Klumper et al , 1995) showed that the MTT chemosensitivity assay may be a good predictor of clinical outcome in acute leukaemia of childhood, and a retrospective study in adult AML also demonstrated the prognostic value of the MTT assay (Sargent & Taylor, 1989).…”
mentioning
confidence: 99%